Effects of Pomegranate Peel (Punica granatum L.) Extract as an Anthelmintic - Monica Amelia; Diana K Jasaputra; Rita Tjokropranoto (Universitas Kristen Maranatha, 2017)
Helminths infections caused by Soil-Transmitted Helminths (STH) are found in manypeople living in developing countries, especially in rural areas. People often use pomegranate asan anthelmintic. The aim of this research is to find out the effects of pomegranate peel (Punicagranatum L.) as an anthelmintic to female Ascaris suum in vitro. The research on the effects ofpomegranate peel extract has been conducted on 900 female Ascaris suum in vitro. Ascaris suumare divided into 5 groups, group I: pomegranate peel extract of dose 25%, group II: pomegranatepeel extract of 50%, group III: pomegranate peel extract of 75%, group IV: 0.9% NaCl as anegative control, and group V is given mebendazole 0.5% as a positive control. The meanpercentage of dead worms in group I is 39%, in group II 61%, while in group III 82%, but itspotential is lower than mebendazole, which kills 100%. The treatment using pomegranate peelextract of 25%, 50% and 75% respectively has significant differences with p < 0.05 againstnegative control (NC) using a 0.9% NaCl. The research concludes that the pomegranate peelextract has an anthelmintic effect against Ascaris suum females in vitro.Keywords: pomegranate peel extract, anthelmintic effect, in vitro